TiO2 coatings doped with MoS2 nanoparticles using plasma electrolytic oxidation on Ti–6Al–4V alloy: Application for enhanced and functional bio-implant surface - Sidra Sadaf Nisar; Han-Cheol Choe (Journal of Materials Research and Technology)
The focus of this study was to examine the surface, mechanical, corrosion, and bioactive characteristics of TiO2 coatings doped with different grams of nanoparticles of MoS2, which were fabricated using the plasma electrolytic oxidation (PEO) technique, and the structure, morphology, surface characteristics, and corrosion resistance of MoS2 and TiO2 coatings were assessed. The coatings were fabricated on the Ti-6Al-4V alloy substrate using a PEO setup, with varying concentrations of MoS2 nanoparticles incorporated into the electrolyte solution. FESEM, XRD, and AFM were utilized to analyze the surface characteristics of the coatings. Also, PDP and AC impedance tests were done to check corrosion properties. Raman analysis, XPS, and cell tests were also done. The findings demonstrated that incorporating MoS2 nanoparticles resulted in creating a composite coating characterized by adequately increased surface energy, wettability, and improved adhesion to the substrate. The FESEM analysis revealed a uniform dispersion of MoS2 throughout the TiO2 matrix forming a homogeneous and compact coating structure and also doping inside the PEO pores. XRD analysis confirmed the presence of TiO2, and the addition of MoS2 nanoparticles further improved the crystallinity of the TiO2 coating. AFM measurements demonstrated a slight increase in surface roughness and an increase in surface hardness upon the inclusion of MoS2. Compared to pure TiO2, the TiO2 coating doped with MoS2 displayed superior electrochemical corrosion resistance and cell proliferation properties. Alazirin staining, ALP, and mRNA activity showed that lower MoS2 content such as P–2MoS2 to P–6MoS2 showed better cellular differentiation properties.